IMPLEMENTATION OF DEEP LEARNING-BASED CURRICULUM: READINESS OF ELEMENTARY SCHOOL TEACHERS - Sudirman, Sudirman; Firdaus, Firdaus; Mujahidah, Mujahidah; Jafar, Muhammad Idris (Universitas Labuhanbatu, 2025)
Purpose- The effectiveness of learning, mainly when it adopts innovative approaches such as deep learning, is greatly influenced by teachers' readiness. This study aims to investigate the readiness of primary school teachers to understand and implement a curriculum based on the principles of deep learning. Methodology- A qualitative research approach with a phenomenological design was used to explore teachers' experiences and perspectives. This study involved nine teachers from various grade levels in five primary schools in Cina Subdistrict, Bone Regency. Data were collected through in-depth interviews. Interview transcripts were analysed using NVivo 12 software. This analysis follows the model of data reduction, data presentation, and conclusion drawing to ensure the validity and credibility of the research results.Findings- Teachers regard deep learning as active and discovery-based, but their readiness remains limited due to insufficient training, weak dissemination, and dependence on support from colleagues, schools, communities, and government. Deep learning adoption will remain uneven due to weak support networks, reliance on a few facilitators, and teacher resistance. Stronger collaboration and sustained professional development are required to address these challenges. Contribution- The findings of this study confirm the extent to which teachers are prepared to implement deep learning approaches in primary schools. This provides empirical evidence of the need for continuous professional development for teachers, especially in adopting learning innovations. The results of this study serve as a recommendation to the government of Bone Regency to take strategic steps to accelerate the effective implementation of deep learning in primary schools.